2002
DOI: 10.1128/jcm.40.10.3871-3873.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dialister pneumosintes Associated with Human Brain Abscesses

Abstract: In this report, we review two cases of brain infection due to Dialister pneumosintes in previously healthy patients. The bacterium was isolated from the first patient by blood culture and directly from a brain abscess in the second patient. In both cases, the infection was suspected to be of nasopharyngeal or dental origin. The patients had favorable outcomes following surgical debridement and antibiotic treatment. After in vitro amplification and partial sequencing of the 16S rRNA gene, two strains were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 19 publications
3
34
0
2
Order By: Relevance
“…Arguably, these lesions could serve as the primary infective focus for the dissemination and subsequent seeding of bacteria into an end organ site. For a majority of episodes, the absence of other detectable infective foci led researchers to conclude that the oral cavity, by default, is the primary source of infection (57,61,63,67,86,88,114,126,139). However, these studies, mainly case reports, suggest a relationship between pyogenic CNS infections and an oral origin of bacteria such as Abiotrophia spp., Dalister pneumosintes, Streptococcus intermedius, S. oralis, Streptococcus constellatus, Fusobacterium spp., F. nucleatum, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis (57,61,63,67,86,88,114,126,139).…”
Section: Cnsmentioning
confidence: 95%
“…Arguably, these lesions could serve as the primary infective focus for the dissemination and subsequent seeding of bacteria into an end organ site. For a majority of episodes, the absence of other detectable infective foci led researchers to conclude that the oral cavity, by default, is the primary source of infection (57,61,63,67,86,88,114,126,139). However, these studies, mainly case reports, suggest a relationship between pyogenic CNS infections and an oral origin of bacteria such as Abiotrophia spp., Dalister pneumosintes, Streptococcus intermedius, S. oralis, Streptococcus constellatus, Fusobacterium spp., F. nucleatum, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis (57,61,63,67,86,88,114,126,139).…”
Section: Cnsmentioning
confidence: 95%
“…More rarely, D. pneumosintes has been isolated from bite wound infections, during respiratory tract and head and neck infections (7,9), from amniotic fluid and placenta samples (6), in human brain abscesses (18), and during bacteremia (12,18). D. invisus has also been identified in urinary tract specimens from renal transplant recipients (4).…”
mentioning
confidence: 99%
“…has been greatly improved by culture-independent studies, mainly focused on oral flora (2,(15)(16)(17)19), comprehensive microbiological information on Dialister spp. remains relatively scarce and antimicrobial susceptibility data are available for only a few isolates (8,18).…”
mentioning
confidence: 99%
“…Lepargneur et al reported D. pneumosintes bacteremia in a young woman with suppurative thrombosis of the ovarian veins. In addition, Rousee et al described two cases of central nervous system infection caused by D. pneumosintes (19). The first case involved a young man with a subdural abscess adjacent to the right frontal lobe in whom D. pneumosintes infection was diagnosed on a blood culture.…”
Section: Pneumosintes Formerly Bacteroides Pneumosintes Is An Obmentioning
confidence: 99%